Diversity, consumption dynamics and ethnomedical claims of traditional leafy vegetables consumed by a rural community in the KwaMbonambi area, northern KwaZulu-Natal, South Africa - Ngcebo Mncwango; Sydney Mavengahama; Nontuthuko Ntuli; Corlina Van Jaarsveld (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Mncwango NC, Mavengahama S, Ntuli NR, van Jaarsveld CM. 2020. Diversity, consumption dynamics and ethnomedical claims of traditional leafy vegetables consumed by a rural community in the KwaMbonambi area, northern KwaZulu-Natal, South Africa. Biodiversitas 21: 1196-1202. Traditional leafy vegetables  (TLVs) are mostly wild and informally-domesticated edible plant species. Their nutritious leaves, shoot tips, flowers and fruits are consumed as vegetables, particularly by rural communities in Africa. However, their consumption and cultivation are still marginal. This study aimed to identify the most preferred TLVs, as well as factors that affect the consumption and cultivation of these species. A questionnaire was administered among 100 respondents to record the preferred TLVs; the reason (s) for preference; consumption frequency; and constraints towards consumption of these vegetable species. This study recorded a total of 18 TLVs that belong to 14 genera and 11 families. Among these, Amaranthus hybridus, A. spinosus, A. thunbergii, Bidens biternata and Corchorus olitorius were the most preferred species. Vegetables were preferred primarily based on the taste; where most people ate them once a week when they are available. The major TLV consumption constraints were seasonal availability and low shelf life. A decline in the availability of TLVs was primarily caused by drought. Regardless of the observed decline, only 23% of respondents practiced informal cultivation of Amaranthus species. Bidens pilosa, Momordica balsamina, and Corchorus olitorius vegetable species were also known to possess some medicinal values. Future research on improving taste, increasing edible plant parts and elongating shelf life for preferred TLVs, is a necessity.